Pathogenicity of Eimeria mivati Inoculation in Broiler Chicken - M Hasan (Jurnal Kedokteran Hewan, 2009)
The propagation of E. mivati local strain was used single cell inoculation.  The objective of this study was to determine the pathogenicity of Eimeria mivati inoculation in broiler chicken by measuring the growth rate, oocysts production and levels of changes in small intestine.  The chickens were devided into two age groups of infection, three and teen days old.  Each group was received 1x104, 1x105   and 1x106  oocysts/chick.  The chichen were raised in wire cages and sampled accordingly.  Data collected was analyzed using analysis of variance. A large number of oocysts production, intestinal villi lesions and depression of growth rate were seen after infection.  Most of the peak production of oocysts were accured after the 9th day of infection.  However, after the peak production of oocysts,  oocysts production decreased extremely.  The choice of parasitic development were in the surface epithelial cells of the villi and the region dominantly effected was the third anterior of small intestine. The result revealed no significant differences regarding photogenicity findings (P0.05) between chicken aged three and ten days after infected with E. mivati.